2020
DOI: 10.1259/bjro.20200033
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiological course in coronavirus disease-19 (COVID-19) patients who are asymptomatic at admission

Abstract: Objective: The study aimed to describe the clinical and imaging course of reverse transcriptase polymerase chain reaction) confirmed coronavirus disease (COVID-19) patients who are asymptomatic at admission. Methods: This was a retrospective observational study. Severe acute respiratory syndrome coronavisrus-2 (SARS-CoV-2) positive cases that were asymptomatic at admission were retrospectively enrolled. Specific clinical information, laboratory test results, chest CT imaging features and outcome data during ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
8
0
2
Order By: Relevance
“…The preliminary reports suggest that pulmonary parenchymal abnormalities do not completely resolve in all the survivors of COVID-19, and in some, the initial inflammation progresses into lung fibrosis [5]. A few published studies have assessed the temporal course of pulmonary findings in COVID-19 pneumonia, but they have mainly focused on the short-term changes in pulmonary opacities, usually up to 4 weeks [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary reports suggest that pulmonary parenchymal abnormalities do not completely resolve in all the survivors of COVID-19, and in some, the initial inflammation progresses into lung fibrosis [5]. A few published studies have assessed the temporal course of pulmonary findings in COVID-19 pneumonia, but they have mainly focused on the short-term changes in pulmonary opacities, usually up to 4 weeks [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the typical chest radiographic findings in asymptomatic patients might not be a definite indication for transfer of patients to the hospital and might not predict the course of disease. Parry, et al [19] reported that asymptomatic infection could have a variable clinicalradiological course, spanning resolution, progression and no change. However, in the progression group, patients also had high levels of C-reactive protein and L-delactohydrogenase, as well as lower lymphocyte counts.…”
Section: A B C Issn 2672-9393mentioning
confidence: 99%
“…Many infected patients do not develop any symptoms. 19-50% patients have been reported to have an asymptomatic infection [12]. Asymptomatic patients act as covert transmitters and constitute a potential contagious source of SARS-CoV-2 as they unknowingly transmit the virus to others [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%